2021
DOI: 10.3389/fpls.2020.600069
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the Cuticular Transpiration Barrier in Response to Water Shortage and Resupply in Camellia sinensis: A Role of Cuticular Waxes

Abstract: The cuticle is regarded as a non-living tissue; it remains unknown whether the cuticle could be reversibly modified and what are the potential mechanisms. In this study, three tea germplasms (Wuniuzao, 0202-10, and 0306A) were subjected to water deprivation followed by rehydration. The epicuticular waxes and intracuticular waxes from both leaf surfaces were quantified from the mature 5th leaf. Cuticular transpiration rates were then measured from leaf drying curves, and the correlations between cuticular trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Since the cuticle is generally regarded as a nonliving tissue, the question is whether the cuticle modification is reversible once the stress conditions (such as drought) have disappeared. Zhang et al (2021) reported that wax coverage and cuticular transpiration barriers indeed are reinforced by drought, but can be reversed following rehydration treatment (Figures 4A,B). There are multiple potential nonexclusive mechanisms working together to regulate cuticular wax deposition, including in vivo wax synthesis or transport in epidermal cells, dynamic phase separation between the EWs and the IWs, in vitro polymerization (Spencer et al, 1988), and retro transportation into epidermal cell wall or cytoplasm for further transformation (Figure 5; Zhang et al, 2021).…”
Section: Developmental and Environmental Modification Of Tea Cuticle And Cuticular Waxmentioning
confidence: 87%
See 3 more Smart Citations
“…Since the cuticle is generally regarded as a nonliving tissue, the question is whether the cuticle modification is reversible once the stress conditions (such as drought) have disappeared. Zhang et al (2021) reported that wax coverage and cuticular transpiration barriers indeed are reinforced by drought, but can be reversed following rehydration treatment (Figures 4A,B). There are multiple potential nonexclusive mechanisms working together to regulate cuticular wax deposition, including in vivo wax synthesis or transport in epidermal cells, dynamic phase separation between the EWs and the IWs, in vitro polymerization (Spencer et al, 1988), and retro transportation into epidermal cell wall or cytoplasm for further transformation (Figure 5; Zhang et al, 2021).…”
Section: Developmental and Environmental Modification Of Tea Cuticle And Cuticular Waxmentioning
confidence: 87%
“…Another advantage of the TEM method is that the cuticle thickness on the adaxial and the abaxial surface can be measured simultaneously. Zhang et al (2021) applied the TEM method and measured the cuticle thickness of the fifth leaf from eight different tea germplasms, and the data were summarized in Table 1. The average thickness of the adaxial cuticle is in the range of 2.12-2.99 µm and the abaxial cuticle thickness is in the range of 1.24-1.46 µm.…”
Section: Tea Cuticle Surface Structurementioning
confidence: 99%
See 2 more Smart Citations
“…A mixture of different long-chain aliphatic molecules, such as alkanes, alcohols, aldehydes, fatty acids, and esters, are present in the cuticle, together with variable amounts of cyclic compounds (Jetter and Riederer, 2016 ). There is controversy about the role of intra- vs. epi-cuticular waxes as barrier to leaf transpiration (Jetter and Riederer, 2016 ; Zeisler-Diehl et al, 2018 ; Zhang et al, 2021 ), but recent evidence suggests that their importance may be specific to leaf side (Zhang et al, 2020 ) and species, which respond plastically to drought (Chen et al, 2020 ; Sanjari et al, 2021 ). Additionally, variable amounts of phenolic compounds have been recovered in the cuticle of different organs and plant species (Karabourniotis and Liakopoulos, 2005 ; España et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%